Microstructures and dielectric relaxation behaviors of pure and tellurium doped CaCu3Ti4O12ceramics prepared via vibro-milling method - Worawut Makcharoen (2018)
In this work, we have reported microstructures and the dielectric properties of CaCu3Ti4O12(CCTO) ceramics doped with different proportions of TeO2dopant (mol%, x=0, 0.5%, 1.0%, 2.0%). The pure and tellurium doping CCTO ceramics were prepared by a conventional solid-state reaction method and the effects of TeO2doping on the electrical properties and microstructures of these ceramics were investigated. XRD analysis confirmed the formation of single-phase material in samples. Scanning electron microscopy (SEM) is used in the micro structural studies of the specimens, which showed that TeO2doping can reduce the mean grain size and increasing size of an abnormal grain growth. Lattice parameter increases slightly with tellurium doping in CCTO, the dielectric constant reached a value as high as 18,000 (at 1 kHz) at a tellurium-doping concentration of 2.0 mol% and showed temperature stability at high frequency. The loss tangent of Te-doped CCTO ceramics was less than 0.05 at 1 kHz region below 105 °C. The loss tangent properties could be interpreted by the internal barrier layer capacitor model and the impedance measurement data. © 2012 Elsevier Ltd and Techna Group S.r.l.